Composite lithium supplementing material and preparation method thereof, positive electrode material and secondary battery
By using composite lithium supplement materials in the battery, and using the combination of lithium-rich particles with incomplete particle sizes and dissociation matrix, the problem that existing lithium supplement agents cannot continuously supplement lithium is solved, and the battery's full life cycle lithium supplement and cycle stability is improved.
Patent Information
- Application Number
- CN202411905674.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
The existing lithium supplement agents cannot continuously supplement lithium, resulting in a decrease in battery cycle stability and the inability to achieve lithium supplementation throughout the life cycle.
A composite lithium supplement material is used, which consists of multiple lithium-rich particles with incomplete particle sizes and a dissociation matrix. The lithium-rich particles release lithium in sequence as the dissociation of the dissociation matrix to achieve slow release of lithium ions.
It realizes lithium supplementation for the entire life cycle of the battery, improves the cycle stability of the battery, maintains the abundance of lithium ions in the battery system, and ensures the high capacity and long cycle characteristics of the battery material.
Smart Images

Figure CN119695159A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery. Background Art
[0002] During the first charge and discharge of a liquid lithium-ion battery, the lithium ions released from the positive electrode material react with the electrolyte to form a solid electrolyte interface (SEI) on the surface of the negative electrode material. This process will irreversibly consume more than 10% of the lithium source in the positive electrode material, making the first-week coulomb efficiency of the lithium-ion battery less than 90%, and will continue to consume the active lithium in the positive electrode during the charge and discharge cycle of the lithium-ion battery, resulting in a shortened life of the lithium-ion battery.
[0003] In response to this phenomenon, the current solution is to add appropriate lithium-rich materials (lithium supplements) to the positive electrode active materials, and reduce lithium loss during the cycle by decomposing the lithium-rich materials to release active lithium during battery charging. In the prior art, when lithium-rich materials are added to batteries as lithium supplements, most of them completely release lithium in the formation stage, which means that the lithium supplement only has a single lithium supplement effect on the battery; however, since the battery will still produce active lithium loss in the subsequent cycle process, the lithium supplement in the prior art cannot continue to supplement lithium to the battery, resulting in a decrease in the cycle stability of the battery in the prior art. Therefore, how to achieve continuous lithium supplementation of the lithium supplement to achieve lithium supplementation for the entire life cycle of the battery has become the key. Summary of the invention
[0004] The purpose of the present invention is to provide a composite lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery, so as to solve the problem that the existing lithium supplement agents cannot continuously supplement lithium.
[0005] To achieve the purpose of the present invention, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a composite lithium supplement material, comprising a plurality of lithium-rich particles and a dissociation matrix, wherein the plurality of lithium-rich particles are distributed in the dissociation matrix, the particle sizes of the plurality of lithium-rich particles are not all the same, and the plurality of lithium-rich particles release lithium in sequence as the dissociation matrix dissociates.
[0007] In one embodiment, the lithium-rich particles include at least first lithium-rich particles and second lithium-rich particles, and the particle size of the first lithium-rich particles is larger than the particle size of the second lithium-rich particles.
[0008] In one embodiment, the first lithium-rich particles and the second lithium-rich particles are randomly distributed in the dissociation matrix.
[0009] In one embodiment, along the direction from the center to the surface of the dissociation matrix, the second lithium-rich particles are distributed on the periphery of the first lithium-rich particles.
[0010] In one embodiment, the lithium-rich particles also include at least third lithium-rich particles, the particle size of the third lithium-rich particles is larger than the particle size of the second lithium-rich particles, and smaller than the particle size of the first lithium-rich particles, and along the direction from the center to the surface of the dissociation matrix, the third lithium-rich particles are distributed on the periphery of the first lithium-rich particles, and the second lithium-rich particles are distributed on the periphery of the third lithium-rich particles.
[0011] In one embodiment, the particle size of the lithium-rich particles satisfies at least two of the ranges of 50 nm to 10 μm.
[0012] In one embodiment, the particle size of the first lithium-rich particles satisfies at least one of 100 nm to 5 μm.
[0013] In one embodiment, the particle size of the second lithium-rich particles satisfies at least one of 50 nm to 1 μm.
[0014] In one embodiment, the mass ratio of the first lithium-rich particles to the second lithium-rich particles is 100:(10-50).
[0015] In one embodiment, the dissociation matrix includes a plurality of coating layers, and the plurality of coating layers together form a multi-layer core-shell structure, and each of the coating layers is dispersedly filled with lithium-rich particles.
[0016] In one embodiment, the composite lithium-supplementing material further includes a plurality of one-dimensional supports extending from the surface of the dissociation matrix, one end of the one-dimensional support extending into the thermal dissociation matrix to connect with the lithium-rich particles, and the other end of the one-dimensional support extending outward away from the dissociation matrix.
[0017] In one embodiment, the dissociated matrix is one or more of a macromolecular polymer, a metal compound, and a carbon material.
[0018] In one embodiment, the dissociation matrix is a porous structure, and the porosity of the dissociation matrix is 50% to 90%.
[0019] In one embodiment, the one-dimensional support comprises metal oxide and / or metal element.
[0020] In one embodiment, the ratio of the length of the one-dimensional support to the radius of the dissociation matrix is (2-10):1.
[0021] In one embodiment, the mass ratio of the lithium-rich particles, the dissociated matrix, and the one-dimensional support is 100:(
[0022] 10~30):(1~10).
[0023] In a second aspect, the present invention provides a method for preparing a composite lithium-supplementing material, comprising: mixing a lithium-rich material with ball milling beads of different diameters to obtain a plurality of lithium-rich particles with different particle sizes; mixing the plurality of lithium-rich particles with a dissociation material precursor so that the plurality of lithium-rich particles are distributed in the dissociation matrix.
[0024] In a third aspect, the present invention provides a positive electrode material, which includes an active material and the composite lithium supplement material as described in the first aspect, or includes a composite lithium supplement material obtained by the preparation method of the lithium supplement material as described in the second aspect.
[0025] In a fourth aspect, the present invention provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode and the negative electrode are arranged in the electrolyte, and the positive electrode comprises the positive electrode material as described in the third aspect.
[0026] In order to solve the above technical problems, the present invention provides a composite lithium replenishing material that can realize lithium replenishment for the battery throughout its life cycle. By distributing lithium-rich particles with different particle sizes in a dissociation matrix, during the circulation process in the composite lithium replenishing material, the lithium-rich particles with smaller particle sizes can be decomposed and release lithium first, and the lithium-rich particles with larger particle sizes can be decomposed and release lithium later; at the same time, the lithium-rich particles release lithium in sequence with the dissociation of the dissociation matrix, so that lithium ions are slowly released in the subsequent charging process of many cycles, so that the composite lithium replenishing material has a sustained release characteristic, can continuously replenish the active lithium lost by the battery, achieve the purpose of lithium replenishment throughout the life cycle, improve the cycle stability of the battery, thereby maintaining the abundance of lithium ions in the battery system, and can ensure that the battery material has the characteristics of high capacity and long cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 is a schematic cross-sectional view of a composite lithium supplement material according to an embodiment;
[0029] Figure 2 is a cross-sectional schematic diagram of a composite lithium supplement material according to another embodiment;
[0030] Figure 3 is a schematic diagram of a partial structure of a composite lithium supplement material according to an embodiment;
[0031] Figure 4 The present invention is a flow chart of a method for preparing a composite lithium supplement material according to an embodiment of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in the present invention includes any and all combinations of one or more of the related listed items.
[0034] It should be noted that the "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0035] All steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b, etc.
[0036] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0037] The present invention provides a composite lithium supplement material, please refer to Figure 1-Figure 3 .
[0038] In one implementation, please refer to Figure 1 and Figure 2 The composite lithium supplement material includes a plurality of lithium-rich particles 10 and a dissociation matrix 20 . The plurality of lithium-rich particles 10 are distributed in the dissociation matrix 20 . The particle sizes of the plurality of lithium-rich particles 10 are not all the same. The plurality of lithium-rich particles 10 release lithium in sequence as the dissociation matrix 20 dissociates.
[0039] Specifically, the lithium-rich particles 10 are composed of lithium-rich materials, and the lithium-rich particles 10 are the main body for lithium supplementation, which can contribute a large amount of lithium ions. During the first charging process, the lithium (Li) in the lithium-rich particles 10 can be released and migrated to the negative electrode of the battery to offset the irreversible lithium loss caused by the formation of the SEI film, thereby increasing the total capacity and energy density of the battery. In the prior art, after the lithium-rich material is added to the battery as a lithium supplement, most of them completely release lithium in the formation stage, which means that the lithium supplement only has a single lithium supplement effect on the battery; however, since the battery will still produce active lithium loss in the subsequent cycle process, the lithium supplement in the prior art cannot continue to supplement lithium for the battery, resulting in a decrease in the cycle stability of the battery in the prior art. Therefore, how to achieve continuous lithium supplementation of the lithium supplement agent to achieve full life cycle lithium supplementation of the battery has become the key.
[0040] To solve the above technical problems, the present invention provides a composite lithium supplement material capable of achieving lithium supplementation throughout the entire life cycle of a battery. By dispersing and filling lithium-rich particles 10 with different particle sizes in a dissociation matrix 20, during the cycling process of the composite lithium supplement material, the lithium-rich particles 10 with smaller particle sizes can preferentially decompose and release lithium, and the lithium-rich particles 10 with larger particle sizes can decompose and release lithium later. At the same time, combined with the sequential de-lithiation of the lithium-rich particles 10 as the dissociation matrix 20 decomposes, lithium ions are slowly released during the charging process of subsequent multiple cycles, enabling the composite lithium supplement material to have a slow-release characteristic, continuously supplementing the active lithium lost by the battery, achieving the purpose of lithium supplementation throughout the entire life cycle, improving the cycling stability of the battery, thereby maintaining an abundance of lithium ions in the battery system, and ensuring that the battery material has the characteristics of high capacity and long cycling life.
[0041] In one embodiment, the chemical formula of the lithium-rich particles 10 includes Li x1 C y1 O z1 , where 0 < x1 ≤ 2, y1 > 0, z1 > 0. In a specific embodiment, the lithium-rich particles 10 may include one or more of Li2C2O4 (lithium oxalate), Li2CO3 (lithium carbonate), Li2C3O3 (lithium trioxalate), Li2C4O4 (lithium butynedioate), Li2C6O6, Li2C3O5 (lithium pyruvate), and Li2C4O6.
[0042] In one embodiment, the chemical formula of the lithium-rich particles 10 includes Li x2 M y2 O z2 , where M is at least one element among Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, Sn, etc., 1 ≤ x2 ≤ 8, 0 < y2, 0 < z2 < 7. In a specific embodiment, the lithium-rich particles 10 may include at least one of Li5FeO4, Li6MnO4, Li6CoO4, Li6ZnO4, Li2NiO2, Li2CuO2, Li2CoO2, Li2MnO2, Li2Ni 0.5 Mn 1.5 O4, Li2Ni d Cu (1-d) O2 (0 < d < 1), etc.
[0043] In one embodiment, the chemical formula of the lithium-rich particles 10 includes Li x3 K y3 , where K is at least one element among O, S, P, N, F, B, Se, Te, etc., 1 ≤ x3 ≤ 5, 0 < y3. The binary lithium supplement agent includes but is not limited to at least one of Li2O, Li2O2, Li3N, Li2S, LiF, Li3P, Li2Se.
[0044] In one embodiment, the chemical formula of the lithium-rich particle 10 includes Li 1+x4 A y4 O z4 , where 0 <x4≤1.2,1≤y4<3,z4> 0, A includes at least one of Ni, Fe, Mn, Co, Cr, V, Mo, Ti, Nb, Zr, Cu, and Mg. The lithium-rich particles 10 can be used as a lithium supplement or directly as a positive electrode material. Exemplarily, the lithium-rich particles 10 include at least one of Li2CuO2, Li2NiO2, and Li2MnO2.
[0045] In one embodiment, the lithium-rich particles 10 may also include LiOH (delithiation potential 4.8V), Li4SiO4 (delithiation potential 4.5V), and Li3PO4 (delithiation potential exceeds 4V). In addition, the lithium-rich particles 10 mentioned above may be undoped or modified by doping, or may be surface coated, pre-lithiation treated, etc. These lithium-rich particles 10 have high theoretical capacity and structural stability, can provide abundant lithium ions, effectively supplement the irreversible lithium ions consumed by the formation of SEI film at the negative electrode, and improve the initial efficiency and overall electrochemical performance of the battery.
[0046] In one embodiment, the particle sizes of the multiple lithium-rich particles 10 are not all the same, which means that the composite lithium-supplementing material includes both lithium-rich particles 10 with the same particle size and lithium-rich particles 10 with different particle sizes. It should be noted that in the present invention, the lithium-rich particles 10 with the same particle size have the same lithium release capacity, while the lithium-rich particles 10 with different particle sizes may have different lithium release capacities. For example, the lithium-release rates of the lithium-rich particles 10 with the same particle size may be the same, that is, the multiple lithium-rich particles 10 with the same particle size release lithium at the same time, and their lithium release rates are the same, so the lithium release can be completed within a similar length of time. In addition, the lithium-release rates of the lithium-rich particles 10 with different particle sizes may be different, and the lithium-rich particles 10 with larger particle sizes have more lithium content or better structural stability, so the lithium release time is longer. Of course, the present invention does not limit the release of lithium by all lithium-rich particles 10 with the same particle size at the same time. The present invention can release lithium successively by lithium-rich particles 10 with the same particle size to achieve a sustained release effect. Of course, the present invention can also release lithium successively by lithium-rich particles 10 with different particle sizes to achieve a sustained release effect.
[0047] In one embodiment, among lithium-rich particles 10 with different particle sizes, the particle size variation trend of the lithium-rich particles 10 may be a linear gradual decrease or an irregular continuous decrease. In a specific embodiment, the particle size variation trend of the lithium-rich particles 10 is a linear gradual decrease. Among multiple lithium-rich particles 10 with different particle sizes, the particle size difference of different lithium-rich particles 10 may be the same. For example, the particle sizes of the lithium-rich particles 10 include 10nm, 20nm, 30nm...1000nm, that is, the difference between the two groups of lithium-rich particles 10 with the closest particle sizes is a constant. In other embodiments, the particle size variation of the lithium-rich particles 10 is an irregular continuous decrease. For example, the particle sizes of the lithium-rich particles 10 include 10nm, 13nm, 25nm, 39nm...1027nm, that is, the difference between the two groups of lithium-rich particles 10 with the closest particle sizes is not a constant.
[0048] In one embodiment, the particle sizes of the plurality of lithium-rich particles 10 are not all the same, which means that the particle sizes of the lithium-rich particles 10 distributed in the dissociation matrix 20 are highly dispersed and meet multiple preset particle size ranges, and there is no intersection between any two preset particle size ranges. In a specific embodiment, the particle size range of the lithium-rich particles 10 can be A1 to A n+10 , where n≥1, so within this particle size range, at least a few small ranges such as A1 to A 10 , A 11 ~A 20 ……A n+1 ~A n+10 The particle sizes of the plurality of lithium-rich particles 10 belong to at least two of the plurality of small ranges mentioned above.
[0049] It should be noted that most of the lithium supplements in the prior art are one-time lithium supplements, and the particle size of the lithium supplement is uniform and limited by the ball milling process. The particle size of the lithium supplement in the prior art is mostly a fixed value or close to a modified value. For example, if the particle size of the lithium supplement in the prior art is m, then the particle size of all its particles will be controlled to be m, or mq~m, m~m+p, where q and p can both approach 0. Therefore, the order of decomposition of all particles of the lithium supplement in the prior art is close, and the purpose of sustained-release lithium supplement and full life cycle lithium supplement cannot be achieved. The lithium-rich particles 10 in the composite lithium supplement material provided by the present invention have a wide particle size distribution range, that is, the particle sizes of multiple lithium-rich particles 10 are not all the same, and according to the particle size distribution of the lithium-rich particles 10 from small to large, the lithium-rich particles 10 with different particle sizes are decomposed successively, thereby achieving the purpose of full life cycle lithium supplement.
[0050] In one embodiment, the dissociation matrix 20 is a main body for loading lithium-rich particles 10. The dissociation matrix 20 has a dissociation characteristic in the battery, wherein the dissociation characteristic refers to the ability of the substance to naturally age, thermally decompose, or rupture under the influence of external / internal forces in the battery. In a specific embodiment, the dissociation matrix 20 can age naturally, and the battery will generate heat during the use of the battery, and the heat will accelerate the aging of the dissociation matrix 20, so the aging rate of the dissociation matrix 20 in the battery is faster than that placed in a natural environment. In a specific embodiment, the dissociation matrix 20 can thermally decompose, such as some low molecular weight polymers or carbon materials with a low degree of carbonization, which will decompose in a hot environment. In a specific embodiment, the dissociation matrix 20 can also be broken by force, such as gas production inside the composite lithium supplement material to cause the dissociation matrix 20 to bulge from the inside to the outside. In summary, during the long cycle of the battery, the dissociation matrix 20 will gradually dissociate, so that the lithium-rich particles 10 dispersed therein are gradually exposed and release lithium. By providing the dissociation matrix 20 with lithium-rich particles 10 of different particle sizes, the gradually exposed smaller lithium-rich particles 10 can first decompose with the unexposed lithium-rich particles 10, or first decompose with the incompletely exposed large lithium-rich particles 10.
[0051] In one embodiment, the dissociation matrix 20 includes one or more of a high molecular polymer, a metal compound, and a carbon material. Optionally, the dissociation matrix 20 includes a polymer material, specifically including one or more of polythiophene, polyacetylene, polyacrylic acid, and derivatives thereof. In a specific embodiment, the dissociation matrix 20 includes a conductive polymer material, specifically including one or more of polyaniline, polypyrrole, and polyaminoindole. Optionally, the dissociation matrix 20 includes a metal oxide, a metal sulfide, and the like. Optionally, the shape of the dissociation matrix 20 can be spherical, capsule-shaped, rod-shaped, and the like.
[0052] In one embodiment, the particle size of the lithium-rich particles 10 satisfies at least two of 50nm to 10μm. It should be explained that the particle sizes of multiple lithium-rich particles 10 are all within the above range, and there are at least two types of lithium-rich particles 10 whose particle sizes satisfy two particle size values within the range or are close to the two particle size values. In a specific embodiment, the particle size of the lithium-rich particles 10 satisfies at least three or more of 1μm to 3μm. Satisfying that the particle size of the lithium-rich particles 10 is within the above range and has more than two particle size values can make the particle size of the lithium-rich particles 10 have a higher particle size distribution range, so as to achieve the purpose of lithium replenishment throughout the life cycle by using different particle sizes. When the particle size range of the lithium-rich particles 10 is too narrow, the particle sizes of multiple lithium-rich particles 10 are close, making it difficult to achieve the purpose of lithium replenishment throughout the life cycle. When the particle size range of the lithium-rich particles 10 is too wide, the particle size of the composite lithium replenishment material is too large, and the compaction density of the positive electrode sheet is affected. Optionally, the particle size of the lithium-rich particles 10 may also meet 50nm-1μm, 50nm-3μm, 1μm-2μm, 1μm-5μm, 1μm-10μm, 3μm-10μm, 5μm-10μm.
[0053] In one implementation, please refer to Figure 1 and Figure 2 , the lithium-rich particles 10 at least include a first lithium-rich particle 11 and a second lithium-rich particle 12, the particle size of the first lithium-rich particle 11 is larger than the particle size of the second lithium-rich particle 12, and the first lithium-rich particle 11 and the second lithium-rich particle 12 are randomly distributed in the dissociation matrix 20. Specifically, the lithium-rich particles 10 include particles of two particle sizes, namely the first lithium-rich particles 11 and the second lithium-rich particles 12. In a specific embodiment, the first lithium-rich particles 11 and the second lithium-rich particles 12 are particles belonging to two particle size ranges, respectively, and the number of the first lithium-rich particles 11 can be multiple, and the multiple first lithium-rich particles 11 all belong to the corresponding particle size range, and the number of the second lithium-rich particles 12 can be multiple, and the multiple second lithium-rich particles 12 all belong to the corresponding particle size range.
[0054] It should be noted that the disordered distribution of the first lithium-rich particles 11 and the second lithium-rich particles 12 refers to the irregular distribution (or random distribution) of the two particles. In a specific embodiment, the two disorderly distributed particles decompose and release lithium as the dissociation matrix 20 dissociates, and the first lithium-rich particles 11 and the second lithium-rich particles 12 are exposed with the same probability, and the exposed first lithium-rich particles 11 and the second lithium-rich particles 12 release lithium at the same time, while the second lithium-rich particles 12 with a smaller particle size decompose faster.
[0055] In one implementation, please refer to Figure 2The lithium-rich particles 10 at least include a first lithium-rich particle 11 and a second lithium-rich particle 12. The particle size of the first lithium-rich particle 11 is larger than that of the second lithium-rich particle 12. In the direction from the center to the surface of the dissociation matrix 20, the second lithium-rich particles 12 are distributed on the periphery of the first lithium-rich particles 11. Specifically, based on the difference between the first lithium-rich particles 11 and the second lithium-rich particles 12, the first lithium-rich particles 11 and the second lithium-rich particles 12 can also be distributed in an orderly manner. Among them, the first lithium-rich particles 11 are mainly distributed in the central area of the dissociation matrix 20, and the second lithium-rich particles 12 are mainly distributed in the surface area of the dissociation matrix 20.
[0056] In one embodiment, the distribution pattern of the first lithium-rich particles 11 and the second lithium-rich particles 12 can also be that in the direction from the center of the dissociation matrix 20 to its surface, the content of the first lithium-rich particles 11 gradually decreases, and the content of the second lithium-rich particles 12 gradually increases, so that the content of the second lithium-rich particles 12 is the highest at the surface close to the dissociation matrix 20 and the lowest at the surface far from the dissociation matrix 20; the content of the first lithium-rich particles 11 is the lowest at the surface close to the dissociation matrix 20 and the highest at the surface far from the dissociation matrix 20.
[0057] In one implementation, please refer to Figure 2 , the lithium-rich particles 10 at least include a third lithium-rich particle 13, the particle size of the third lithium-rich particle 13 is larger than the particle size of the second lithium-rich particle 12, and smaller than the particle size of the first lithium-rich particle 11, and along the direction from the center of the dissociation matrix 20 to the surface, the third lithium-rich particles 13 are distributed on the periphery of the first lithium-rich particles 11, and the second lithium-rich particles 12 are distributed on the periphery of the third lithium-rich particles 13. Optionally, the first lithium-rich particles 11, the second lithium-rich particles 12 and the third lithium-rich particles 13 are particles belonging to three particle size ranges respectively, and the number of the third lithium-rich particles 13 can be multiple, and the multiple third lithium-rich particles 13 all belong to their corresponding particle size ranges. In a specific embodiment, the particle size range corresponding to the third lithium-rich particle 13 is not the intersection of the particle size ranges corresponding to the first lithium-rich particle 11 and the second lithium-rich particle 12.
[0058] Optionally, in the direction from the center of the dissociation matrix 20 to its surface, the dissociation matrix 20 includes a central region, a middle region and an outer region in sequence, the middle region surrounds the central region, and the outer region surrounds the middle region. The first lithium-rich particles 11 are distributed in the central region, the third lithium-rich particles 13 are distributed in the middle region, and the second lithium-rich particles 12 are distributed in the outer region.
[0059] In one embodiment, the particle size of the first lithium-rich particle 11 satisfies at least one of 100 nm to 5 μm. Specifically, there may be multiple first lithium-rich particles 11, and the particle sizes of the multiple first lithium-rich particles 11 satisfy the range and the particle size values are not all the same. The particle size of the first lithium-rich particle 11 is within the above range to ensure that the first lithium-rich particle 11 has a larger particle size, so that post-decomposition lithium can be achieved. When the particle size of the first lithium-rich particle 11 is too small, the particle size of the first lithium-rich particle 11 approaches that of the second lithium-rich particle 12, thereby failing to achieve the purpose of lithium replenishment throughout the life cycle. When the particle size of the first lithium-rich particle 11 is too large, the first lithium-rich particle 11 occupies the space of the second lithium-rich particle 12, resulting in a reduction in the content of the second lithium-rich particle 12, resulting in insufficient lithium replenishment capacity in the early stage, and also affecting the particle size of the composite lithium replenishment material. The compaction density of the positive electrode sheet is affected. Optionally, the particle size of the first lithium-rich particles 11 may be at least one of 100 nm, 200 nm, 500 nm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm.
[0060] In one embodiment, the particle size of the second lithium-rich particle 12 satisfies at least one of 50nm to 1μm. Specifically, there may be multiple second lithium-rich particles 12, and the particle sizes of the multiple second lithium-rich particles 12 meet this range and the particle size values are not all the same. The particle size of the second lithium-rich particle 12 is within the above range to ensure that the second lithium-rich particle 12 has a smaller particle size, so that lithium can be separated first. When the particle size of the second lithium-rich particle 12 is too small, the dispersion difficulty of the second lithium-rich particle 12 increases, which is not conducive to the preparation of composite lithium supplement materials. When the particle size of the second lithium-rich particle 12 is too large, the particle size of the second lithium-rich particle 12 approaches that of the first lithium-rich particle 11, so that the purpose of lithium supplementation throughout the life cycle cannot be achieved. Optionally, the particle size of the second lithium-rich particle 12 may be at least one of 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, and 1μm.
[0061] In one embodiment, when the dissociation matrix 20 is spherical or quasi-spherical, the radius of the dissociation matrix 20 is 600nm to 11μm. It should be noted that the lithium-rich particles 10 are all distributed in the dissociation matrix 20, so the radius of the dissociation matrix 20 actually refers to the overall radius of the composite material composed of the dissociation matrix 20 and the lithium-rich particles 10. The radius of the dissociation matrix 20 is within the above range to accommodate more lithium-rich particles 10, and the particle size of the lithium-rich particles 10 is matched to ensure that the particle size range of the dispersed lithium-rich particles 10 is larger. When the radius of the dissociation matrix 20 is too small, the content of lithium-rich particles 10 in the dissociation matrix 20 is small, resulting in a decrease in lithium replenishment capacity; and it also limits the upper limit of the particle size of the lithium-rich particles 10, resulting in a smaller upper limit of the particle size of the lithium-rich particles 10, making it difficult to achieve the effect of lithium replenishment throughout the life cycle. When the radius of the dissociation matrix 20 is too large, the migration efficiency of lithium ions will be affected, and gelation is likely to occur after the residual alkali on the surface of the lithium-rich particles 10 absorbs water. Optionally, the radius of the dissociation matrix 20 may be 600 nm, 800 nm, 1 μm, 3 μm, 5 μm, 6 μm, 9 μm, or 11 μm.
[0062] In one embodiment, the mass ratio of the first lithium-rich particles 11 and the second lithium-rich particles 12 is 100:(10-50). Meeting the mass ratio of the first lithium-rich particles 11 and the second lithium-rich particles 12 can ensure that the composite lithium-supplementing material can achieve the effect of gradually releasing lithium and replenishing lithium throughout the life cycle. When the proportion of the first lithium-rich particles 11 is too large, due to the large particle size of the first lithium-rich particles 11, most of the lithium-rich particles 10 in the composite lithium-supplementing material release lithium in the later stage, resulting in a poor lithium replenishment effect in the early stage of the formation stage. When the proportion of the second lithium-rich particles 12 is too large, due to the small particle size of the second lithium-rich particles 12, most of the lithium-rich particles 10 in the composite lithium-supplementing material release lithium in the early stage, resulting in a poor lithium replenishment effect in the later battery cycle process. Optionally, the mass ratio of the first lithium-rich particles 11 and the second lithium-rich particles 12 can be 100:10, 100:20, 100:30, 100:40, 100:50.
[0063] In one implementation, please refer to Figure 2 and Figure 3 , the dissociation matrix 20 includes a plurality of coating layers 21, and the plurality of coating layers 21 together form a multi-layer core-shell structure, and each coating layer 21 is dispersedly filled with lithium-rich particles 10. Specifically, the dissociation matrix 20 is a multi-layer nested core-shell structure composed of a plurality of coating layers 21. In a specific embodiment, the core of the multi-layer nested core-shell structure can be a mixture of the dissociation material and the lithium-rich particles 10, and then a plurality of coating layers 21 are arranged outside the core, and each coating layer 21 is also dispersedly filled with lithium-rich particles 10.
[0064] In one implementation, please refer to Figure 2 and Figure 3, at least one coating layer 21 is a porous cross-linked structure having holes 22. Specifically, the coating layer 21 with a porous cross-linked structure is similar to a fishing net, and the multi-layer coating layer 21 is similar to a multi-layer superimposed fishing net, and the holes 22 are covered by the multi-layer coating. In a specific embodiment, each coating layer 21 has holes 22, and the positions of the holes 22 on two adjacent coating layers 21 may not be completely the same, that is, the holes 22 on two adjacent coating layers 21 may not be connected, or may be partially connected. In this way, the outer coating layer 21 has a shielding effect on the holes 22 on the inner coating layer 21. Optionally, the outermost coating layer 21 on the dissociation substrate 20 may not have holes, thereby completely shielding the holes on the inner coating layer 21.
[0065] The present invention arranges the dissociation matrix 20 into a nested core-shell structure of multiple coating layers 21, so that the dissociation matrix 20 dissociates layer by layer, and during the dissociation process of each coating layer 21, the lithium-rich particles 10 dispersed and filled in the coating layer 21 release lithium replenishment, thereby achieving the effect of lithium replenishment throughout the life cycle; and the coating layer 21 is a porous cross-linked structure with pores 22 to reduce the difficulty of dissociation, and the pores 22 on each coating layer 21 can be covered by the multiple coating layers 21, thereby improving the sealing of the lithium-rich particles 10 in the dissociation matrix 20.
[0066] In one embodiment, the particle size of the lithium-rich particles 10 in any coating layer 21 is the same or similar, and the particle size ranges of the lithium-rich particles 10 in two adjacent coating layers 21 are different. Specifically, in addition to the core, the number of coating layers 21 is two or more, including at least a first coating layer and a second coating layer, the first coating layer is coated on the outer surface of the core, and the second coating layer is coated on the outer surface of the first coating layer, wherein the first coating layer can be the middle layer region in the above embodiment, and the second coating layer can be the outer layer region in the above embodiment. The particle size of the lithium-rich particles 10 filled in the first coating layer is the same or similar, the particle size of the lithium-rich particles 10 filled in the second coating layer is the same or similar, and the particle size ranges of the lithium-rich particles 10 filled in the first coating layer and the second coating layer are different.
[0067] It should be explained that the same or similar particle sizes of the lithium-rich particles 10 filled in the first coating layer means that the particle sizes of the lithium-rich particles 10 in the layer are within the same range. For example, the first coating layer is filled with the first lithium-rich particles 11 provided in the above embodiment, and the particle sizes of the lithium-rich particles 10 filled in the first coating layer should all meet the particle size of the first lithium-rich particles 11. Of course, the same or similar particle sizes of the lithium-rich particles 10 filled in the second coating layer also means that the particle sizes of the lithium-rich particles 10 in the layer are within the same range. Furthermore, the different particle size ranges of the lithium-rich particles 10 filled in the first coating layer and the second coating layer can be understood as the first coating layer is filled with the first lithium-rich particles 11 provided in the above embodiment, and the second coating layer is filled with the second lithium-rich particles 12 provided in the above embodiment, so the ranges of the first lithium-rich particles 11 and the second lithium-rich particles 12 are different.
[0068] In one embodiment, the particle size range of the lithium-rich particles 10 in any coating layer 21 is not the same, and the proportion of large-size lithium-rich particles 10 and small-size lithium-rich particles 10 in any coating layer 21 is different. Specifically, the first coating layer and the second coating layer both include the first lithium-rich particles 11 and the second lithium-rich particles 12, and the mass ratio of the first lithium-rich particles 11 and the second lithium-rich particles 12 in the first coating layer is different from the mass ratio of the first lithium-rich particles 11 and the second lithium-rich particles 12 in the second coating layer. In this way, the mass ratio of the first lithium-rich particles 11 and the second lithium-rich particles 12 in each coating layer 21 is different.
[0069] Optionally, the mass proportion of the first lithium-rich particles 11 in the first coating layer is greater than the mass proportion of the second lithium-rich particles 12, and the mass proportion of the first lithium-rich particles 11 in the second coating layer is less than the mass proportion of the second lithium-rich particles 12. It can be understood that the second coating layer is located on the outer side, so the second coating layer dissociates earlier, and the second lithium-rich particles 12 with smaller particle sizes account for a larger proportion so that they can be decomposed first to achieve lithium replenishment, and the first lithium-rich particles 11 with larger particle sizes account for a smaller proportion so that they can be decomposed later to achieve lithium replenishment. At the same time, the first lithium-rich particles 11 in the second coating layer can cooperate with the second lithium-rich particles 12 in the first coating layer to decompose and achieve lithium replenishment.
[0070] In one implementation, please refer to Figure 1-Figure 3The composite lithium supplement material also includes a plurality of one-dimensional supports 30 extending from the surface of the dissociation matrix 20, one end of the one-dimensional support 30 extends into the dissociation matrix 20 and is connected to the lithium-rich particles 10, and the other end of the one-dimensional support 30 extends outward along the dissociation matrix 20. Specifically, the one-dimensional support 30 is a rod-shaped structure, and the plurality of one-dimensional supports 30 dispersed on the surface of the dissociation material make the composite lithium supplement material form a "sea urchin-type" structure. Most of the lithium supplement agents in the prior art also face the problems of poor dispersibility and easy gelation, wherein the gelation problem is mainly because there will be more residual alkali on the surface of the lithium supplement agent (lithium-rich material). When the residual alkali absorbs water and the lithium supplement agent expands during discharge, the lithium supplement agents adhere to each other, resulting in gelation.
[0071] In one implementation, please refer to Figure 3 , the one-dimensional support 30 extends into the dissociation matrix 20 through the holes 22 on each coating layer 21; the one-dimensional support 30 can be connected to the lithium-rich particles 10 in any coating layer 21. Therefore, part of the one-dimensional support 30 can be connected to the first lithium-rich particles 11 located in the core area of the dissociation matrix 20, or part of the one-dimensional support 30 can be connected to the second lithium-rich particles 12 or the third lithium-rich particles 13 located in the outer area of the dissociation matrix 20.
[0072] The present invention makes the composite lithium supplement material into a "sea urchin-shaped" structure, so that the particles of the composite lithium supplement material have a strong mutual repulsion relationship, and the one-dimensional support body 30 increases the specific surface area of the composite lithium supplement material, thereby avoiding the mutual agglomeration between the particles of the composite lithium supplement material, so that the composite lithium supplement material can be highly dispersed, and the use of dispersants can be reduced. At the same time, the one-dimensional support body 30 can also provide an anti-gel effect, because the particles of the composite lithium supplement material are mutually repelled by the one-dimensional support body 30, and the one-dimensional support body 30 increases the particle size of the composite lithium supplement material. Even if the dissociated material and the lithium-rich particles 10 inside it expand, the dissociated material and the lithium-rich particles 10 inside it are difficult to exceed the length of the one-dimensional support body 30. Even if the residual alkali on the surface of the composite lithium supplement material absorbs water under the influence of the mutual repulsion, the composite lithium supplement materials will not adhere to each other and gel.
[0073] In one embodiment, the surface of the lithium-rich particle 10 has an active group, one end of the one-dimensional support 30 extends into the dissociation matrix 20 through the hole 22 and is connected to the lithium-rich particle 10 through the active group, and the one-dimensional support 30 is catalytic. Specifically, the lithium-rich particle 10 can be grafted with active groups on its surface by surface treatment technology, such as hydroxyl, carboxyl, amino, etc. After the one-dimensional support 30 extends into the dissociation matrix 20, it can be connected to the lithium-rich particle 10, and the connection strength between the two is improved by the active group. Optionally, the one-dimensional support 30 includes a metal oxide and / or a metal element.
[0074] It is understandable that most of the lithium-rich particles 10 provided in the above embodiments have the problem of too high decomposition voltage. The higher decomposition voltage will lead to a decrease in the lithium replenishment capacity of the lithium-rich particles 10, and may cause the lithium-ion battery to produce gas during the first charge and discharge. Therefore, the present invention prepares the catalytic material into a one-dimensional support 30. Under the effect of achieving high dispersion and anti-gel, the one-dimensional support 30 can also provide a catalytic effect for catalyzing the lithium-rich particles 10 to reduce the decomposition voltage, so that the capacity of the lithium-rich particles 10 can be fully released, thereby improving the battery performance.
[0075] In the specific embodiment, please refer to Figure 2 and Figure 3 The composite lithium-supplementing material includes lithium-rich particles 10, a dissociation matrix 20 and a one-dimensional support 30. The lithium-rich particles 10 include a first lithium-rich particle 11, the first lithium-rich particle 11 serves as a lithium-supplementing core, and the dissociation matrix 20 is outside the lithium-supplementing core. The dissociation matrix 20 includes at least a first coating layer 211 and a second coating layer 212, the first coating layer 211 covers the lithium-supplementing core, and the second coating layer 212 covers the first coating layer 211. The third lithium-rich particles 13 are distributed in the first coating layer 211, and the second lithium-rich particles 12 are distributed in the second coating layer 212. The particle size of the first lithium-rich particles 11 is larger than that of the second lithium-rich particles 12, and the particle size of the third lithium-rich particles 13 is larger than that of the second lithium-rich particles 12. Both the first coating layer 211 and the second coating layer 212 have holes 22, and the one-dimensional support 30 extends into the dissociation matrix 20 through the holes 22 and is connected to the lithium-supplementing core (the first lithium-rich particle 11). The surface of the lithium-supplemented core has active groups (such as hydroxyl groups), and the one-dimensional support body 30 is connected to the lithium-supplemented core through the active groups. The dissociation matrix 20 also includes a third coating layer 213, and the third coating layer 213 covers the second coating layer 212. The porosity of the third coating layer 213 is less than that of the second coating layer 212 and the first coating layer 211, that is, the third coating layer 213 has better compactness. The third coating layer 213 is used to block the holes 22 on the surface of the second coating layer 212 after the one-dimensional support body 30 is grown.
[0076] In one embodiment, the porosity of the dissociation matrix 20 is 50% to 90%. Satisfying the porosity of the dissociation matrix 20 within the above range can ensure that the one-dimensional support 30 can extend into the thermal dissociation matrix 20 through the holes 22 and connect with the lithium-rich particles 10. When the porosity of the dissociation matrix 20 is too small, the pore content on each coating layer 21 is too small, making it difficult for the one-dimensional support 30 to grow out of the holes 22. When the porosity of the dissociation matrix 20 is too large, the fixation effect of the lithium-rich particles 10 in the dissociation matrix 20 becomes poor. Optionally, the porosity of the dissociation matrix 20 can be 50%, 60%, 70%, 80%, or 90%.
[0077] In one embodiment, the ratio of the length of the one-dimensional support 30 to the radius of the dissociation matrix 20 is (2 to 10): 1. Satisfying the ratio of the length of the one-dimensional support 30 to the radius of the dissociation matrix 20 within the above range can ensure that the composite lithium supplement material has high dispersibility and high rigidity, and can also effectively reduce the gelation of the composite lithium supplement material. When the length of the one-dimensional support 30 is too short, the dispersibility of the composite lithium supplement material deteriorates, and the dissociation material and its internal lithium-rich particles 10 expand and cause it to exceed the length of the one-dimensional support 30, thereby forming gelation. When the length of the one-dimensional support 30 is too long, the overall volume of the composite lithium supplement material is restricted by the one-dimensional support 30, resulting in an excessively large volume and a low lithium content, and the lithium supplement effect of the composite lithium supplement material deteriorates. Optionally, the ratio of the length of the one-dimensional support 30 to the radius of the dissociation matrix 20 can be 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1.
[0078] In one embodiment, the mass ratio of the lithium-rich particles 10, the dissociation matrix 20, and the one-dimensional support 30 is 100: (10-30): (1-10). Meeting the mass ratio of the lithium-rich particles 10, the dissociation matrix 20, and the one-dimensional support 30 within the above range can ensure that the composite lithium-supplementing material has a higher lithium-supplementing capacity, and ensure that it can have a continuous lithium-supplementing ability for a longer period of time. It can also effectively reduce the decomposition voltage of the lithium-rich particles 10 and reduce the gelation of the composite lithium-supplementing material. When the mass proportion of the dissociation matrix 20 and the one-dimensional support 30 is too large, the content of the lithium-rich particles 10 will be affected, thereby reducing the lithium-supplementing capacity of the composite lithium-supplementing material. When the mass proportion of the dissociation matrix 20 is too small, the dissociation matrix 20 does not completely coat the lithium-rich particles 10, which will result in the continuous lithium-supplementing ability of the composite lithium-supplementing material and affect the battery performance. When the mass ratio of the one-dimensional support 30 is too small, the effect of the one-dimensional support 30 in catalyzing the decomposition voltage drop of the lithium-rich particles 10 becomes poor, and the length of the one-dimensional support 30 is too short to provide an anti-gel effect. Optionally, the mass ratio of the lithium-rich particles 10, the dissociation matrix 20, and the one-dimensional support 30 can be 100:10:(1-10), 100:20:(1-10), 100:30:(1-10), 100:(10-30):1, 100:(10-30):5, 100:(10-30):10.
[0079] The present invention provides a method for preparing a composite lithium supplement material. Figure 4 .
[0080] In one embodiment, the preparation method of the composite lithium supplement material specifically comprises the following steps:
[0081] Step S10, mixing the lithium-rich material and ball milling beads with different diameters and performing ball milling to obtain a plurality of lithium-rich particles with different particle sizes.
[0082] Step S20 , mixing a plurality of lithium-rich particles with a dissociation material precursor, so that the plurality of lithium-rich particles are distributed in a dissociation matrix.
[0083] In one embodiment, in step S10, the lithium-rich material and ball milling beads of different diameters are mixed and ball milled, specifically including: controlling the ball material diameter ratio of the lithium-rich material and the ball milling beads to prepare lithium-rich particles of different particle sizes in batches. Optionally, the types of lithium-rich materials of different particle sizes can be the same or different, and the specific types of lithium-rich materials can refer to the above embodiment, which will not be repeated here.
[0084] In one embodiment, in step S20, the dissociation material precursor may include one or more of polythiophene, polyacetylene, polyacrylic acid and derivatives thereof. In a specific embodiment, the dissociation matrix includes a conductive polymer material, specifically including one or more of polyaniline, polypyrrole and polyaminoindole.
[0085] In one embodiment, in step S20, the dissociation material precursor can also be a precursor of a polymer, for example, the precursor of polythiophene is 3,4-ethylenedioxythiophene, the precursor of polyacetylene is acetylene, and the precursor of polyacrylic acid is acrylic acid; therefore, the dissociation material precursor can include one or more of 3,4-ethylenedioxythiophene, acetylene, and acrylic acid.
[0086] In one embodiment, in step S20, the dissociation material precursor may further include other dopants, such as polymerization initiators, crosslinking agents, etc. In a specific embodiment, the dissociation material precursor may include 3,4-ethylenedioxythiophene, sodium polystyrene sulfonate, a photoinitiator, and p-toluenesulfonic acid, wherein 3,4-ethylenedioxythiophene may be a monomer of polythiophene, sodium polystyrene sulfonate is a para-anion, and the photoinitiator and p-toluenesulfonic acid are dopants.
[0087] In a specific embodiment, in step S20, the dissociated material precursor can also form a cross-linked structure through a cross-linking agent reaction, and the dissociated material of the cross-linked structure can form holes, thereby omitting the pore-making step.
[0088] In one embodiment, in step S20, the dissociation material precursor may also be an inorganic substance, such as a metal compound and / or a carbon material. The inorganic substance and the lithium-rich particles may be compounded together by mechanical ball milling or mixed calcination. Of course, the carbon material may also be obtained by calcining an organic substance.
[0089] In one embodiment, in step S20, the lithium-rich particles and the dissociation material precursor can be mixed multiple times. Specifically, the dissociation matrix can include multiple coating layers. During the preparation process, the lithium-rich particles and the dissociation material precursor can be mixed first to preliminarily anchor the lithium-rich particles in the dissociation material, and then the mixed material is mixed with the dissociation material precursor to form another coating layer of the dissociation material. Moreover, this step can be repeated multiple times so that the lithium-rich particles are completely enclosed and dispersed in the dissociation matrix.
[0090] In one embodiment, in step S20, during the multiple coating processes using the dissociation material precursor, lithium-rich particles of different particle sizes can also be mixed in at the same time, so as to form a distribution pattern in which the particle size of the lithium-rich particles decreases from the inside to the outside. For example, the ball-milled lithium-rich particles include at least first lithium-rich particles, second lithium-rich particles, and third lithium-rich particles, wherein the first lithium-rich particles are first mixed with the dissociation material precursor, and the two form a first mixture. Then, the first mixture, the third lithium-rich particles, and the dissociation material precursor are mixed so that the third lithium-rich particles are distributed on the periphery of the first lithium-rich particles. Then, the second mixture, the second lithium-rich particles, and the dissociation material precursor are mixed so that the second lithium-rich particles are distributed on the periphery of the third lithium-rich particles, thereby forming a multi-layer distribution structure of lithium-rich particles.
[0091] In one implementation, please refer to Figure 4 The preparation method of the composite lithium supplement material specifically includes the following steps:
[0092] Step S30, performing surface etching on the mixture of the dissociated matrix and the lithium-rich particles, and growing a one-dimensional support on the dissociated matrix.
[0093] Step S40, mixing the material having a one-dimensional support with a dissociation material precursor to dissociate the matrix to form a multi-layer core-shell structure.
[0094] In one embodiment, in step S30, the purpose of surface etching the mixture of the dissociation matrix and the lithium-rich particles includes etching holes on the surface of the dissociation matrix, or modifying active groups on the surface of part of the lithium-rich particles. It is understandable that etching holes on the surface of the dissociation matrix can expose the lithium-rich particles on the outer side, so that the exposed lithium-rich particles can be surface modified. Of course, in the case where the dissociation matrix is a cross-linked structure, a porous structure has been formed on the surface of the dissociation matrix during molding, and the purpose of surface etching is mainly to modify active groups on the surface of part of the lithium-rich particles.
[0095] In one embodiment, in step S30, the method of surface etching the mixture of the dissociated matrix and the lithium-rich particles includes liquid etching, solid etching, gas etching, plasma etching, etc. Among them, liquid etching can be to immerse the mixture of the dissociated matrix and the lithium-rich particles in an acid solution or an alkaline solution. Since the stability of the dissociated matrix is poor, holes can be etched on the surface of the dissociated matrix, and the etching liquid can further react with the lithium-rich particles to form active groups on its surface. Solid-state etching can be to mix the mixture with an etchant, the etchant is bound to the surface of the mixture, the etchant is nano-metal compound particles, and the etchant and the mixture are placed in an inert atmosphere for thermal etching. The etchant is heated faster, so the part bound to the dissociated matrix is melted first, so that holes are etched on the surface of the dissociated matrix; then the etchant is bound to the surface of the lithium-rich particles as a modified active group.
[0096] In one embodiment, in step S30, growing a one-dimensional support on the dissociation substrate specifically includes: depositing a catalyst in the pores of the dissociation substrate so that the catalyst forms a one-dimensional support. One end of the one-dimensional support extends into the dissociation substrate through the pores, and the other end of the one-dimensional support extends in a direction away from the dissociation substrate. Specifically, the catalyst can be deposited into the pores of the dissociation substrate by ALD (atomic layer deposition technology), the catalyst is connected to the lithium-rich particles through the active groups on the surface of the particles, and the catalyst grows to form a one-dimensional rod-like structure.
[0097] ALD technology can deposit catalysts on lithium-rich particles in the form of single atoms, and the catalysts are easier to deposit on the basis of active groups on the lithium-rich particles. However, the dissociated matrix is mainly organic matter, so it is difficult for the catalyst to be deposited on the surface of the dissociated matrix through ALD technology, so that the composite lithium-supplementing material forms a "sea urchin-shaped" structure.
[0098] In one embodiment, in step S40, the purpose of coating the prepared material with the dissociated material is to seal the original pores, thereby preventing external water vapor from entering the composite lithium supplement material through the pores.
[0099] The preparation method provided by the present invention ball-mills the lithium-rich material into lithium-rich particles with different particle sizes, and disperses and fills the lithium-rich particles with different particle sizes in a dissociation matrix, so that during the circulation process in the composite lithium-supplementing material, the lithium-rich particles with smaller particle sizes can be decomposed and released lithium first, and the lithium-rich particles with larger particle sizes can be decomposed and released lithium later; at the same time, the lithium-rich particles are dissociated with the dissociation matrix to sequentially release lithium, so that lithium ions are slowly released in the subsequent charging process of many cycles, so that the composite lithium-supplementing material has a sustained release characteristic, can continuously replenish the active lithium lost by the battery, realize the uninterrupted lithium replenishment effect, and improve the cycle stability of the battery, thereby maintaining the abundance of lithium ions in the battery system, and can ensure that the battery material has the characteristics of high capacity and long cycle.
[0100] Furthermore, the present invention also inserts a one-dimensional support body on the dissociation matrix through micro-etching technology and atomic layer deposition technology, and makes the composite lithium supplement material into a "sea urchin-type" structure, so that the particles of the composite lithium supplement material have a strong mutual repulsion relationship. The one-dimensional support body increases the specific surface area of the composite lithium supplement material, thereby avoiding the mutual agglomeration between the particles of the composite lithium supplement material, so that the composite lithium supplement material can be highly dispersed and the use of dispersant can be reduced; at the same time, the one-dimensional support body can also provide an anti-gel effect. Even if the residual alkali on the surface of the composite lithium supplement material absorbs water under the influence of the mutual repulsion effect, the composite lithium supplement material will not stick to each other and gel.
[0101] In one embodiment, the present invention further provides a positive electrode material, the positive electrode material comprising a positive electrode active material and a lithium supplement. The lithium supplement is a composite lithium supplement material provided in the above embodiment. Optionally, the positive electrode active material can be a phosphate positive electrode active material or a ternary positive electrode active material. In a specific embodiment, the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium vanadium phosphate fluoride, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
[0102] In one embodiment, the content of the composite lithium-supplementing material in the positive electrode material can be controlled at 1% to 6% of the mass of the positive electrode active material. This ratio can just make up for the loss of active lithium in the battery during the first charging process. If the amount of composite lithium-supplementing material added to the positive electrode material is too low, the active lithium lost in the positive electrode active material cannot be fully replenished, which is not conducive to improving the energy density and capacity retention rate of the battery. If the amount of composite lithium-supplementing material added to the positive electrode active material is too high, the original reversible capacity will be occupied and the cost will be increased. In some specific embodiments, in the positive electrode material, the mass percentage of the composite lithium-supplementing material can be 1%, 2%, 4%, 6%, etc.
[0103] In one embodiment, the present invention further provides a positive electrode plate, the positive electrode plate includes a current collector and an active material layer disposed on the current collector, the active material layer includes the composite lithium supplement material of any one of the above embodiments. Or the active material layer includes the composite lithium supplement material obtained by the preparation method of the composite lithium supplement material in the above embodiments.
[0104] In one embodiment, the positive electrode sheet includes a positive current collector, and the positive current collector has a positive active layer, and the positive active layer includes components such as positive active materials, composite lithium supplement materials, conductive agents, and binders. The present invention does not specifically limit these materials, and suitable materials can be selected according to actual application requirements. The positive current collector includes but is not limited to any one of copper foil and aluminum foil. The conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes, and the content of the conductive agent in the positive active layer is 3wt% to 5wt%. The types of binders include polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives, and the content of the binder in the positive active layer is 2wt% to 4wt%.
[0105] In one embodiment, the present invention further provides a secondary battery, the secondary battery comprising a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode comprises the above-mentioned positive electrode material; the electrolyte may be an electrolyte solution, in which case the secondary battery further comprises a diaphragm disposed between the positive electrode plate and the negative electrode plate; or, the electrolyte may be a solid electrolyte solution, in which case the secondary battery does not have a diaphragm and is replaced by a solid electrolyte.
[0106] The technical solution of the present invention is described in detail below through specific embodiments.
[0107] Example 1
[0108] This embodiment provides a composite lithium supplement material. Figure 2 As shown, the composite lithium supplement material includes lithium-rich particles (Li2C2O4), a dissociated matrix (polythiophene), and a one-dimensional support (CoO). The lithium-rich particles include at least a first lithium-rich particle, a second lithium-rich particle, and a third lithium-rich particle. The first lithium-rich particle is located in the central region, the third lithium-rich particle is located in the middle region, and the second lithium-rich particle is located in the outer region.
[0109] Among them, the particle size of the lithium-rich particles satisfies 500nm~2μm, the particle size of the first lithium-rich particles is 2μm, the particle size of the second lithium-rich particles is 500nm, and the particle size of the third lithium-rich particles is 1μm. The mass ratio of the first lithium-rich particles, the second lithium-rich particles and the third lithium-rich particles is 100:20:30. The radius of the dissociated matrix is 5μm. The ratio of the length of the one-dimensional support body to the radius of the dissociated matrix is 3:1. The mass ratio of the lithium-rich particles, the dissociated matrix, and the one-dimensional support body is 100:20:7.
[0110] The preparation method of the composite lithium supplement material comprises the following steps:
[0111] 1) By controlling the diameter ratio of lithium-rich material and ball milling beads to 2mm:5nm:10mm=3:4:3, the first lithium-rich particles, the second lithium-rich particles and the third lithium-rich particles with highly dispersed particle sizes are ball milled. According to the ball milling time, the first lithium-rich particles are ball milled for 4h, the second lithium-rich particles are ball milled for 24h, and the third lithium-rich particles are ball milled for 8h.
[0112] 2) Adding lithium-rich particles to a dissociation material precursor, controlling the relative mass ratio, the dissociation material precursor includes 3,4-ethylenedioxythiophene as a monomer, sodium polystyrene sulfonate as a counter anion, and adding a photoinitiator and p-toluenesulfonic acid (TsOH) as a dopant. The mixture of the dissociation matrix and lithium-rich particles is synthesized by reacting in an air atmosphere for 15 minutes, and the dissociation matrix filled with lithium-rich particles is obtained after crushing.
[0113] 3) After surface microetching, relatively long transition metal oxide rod-like structures are grown on the pores of the coating layer using ALD technology.
[0114] 4) Continue coating once to seal all the pores of the initial coating, and the coating amount is 1% to 5% of step 2) to obtain a composite lithium supplement material.
[0115] Example 2
[0116] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the first lithium-rich particles, the second lithium-rich particles, and the third lithium-rich particles are evenly distributed in the dissociation matrix. Figure 1 shown.
[0117] Example 3
[0118] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the particle size of the lithium-rich particles meets 100nm-1μm, the particle size of the first lithium-rich particle is 1μm, the particle size of the second lithium-rich particle is 100nm, and the particle size of the third lithium-rich particle is 200nm.
[0119] Example 4
[0120] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the lithium-rich particles do not include third lithium-rich particles.
[0121] Example 5
[0122] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the radius of the dissociated matrix is 10 μm.
[0123] Example 6
[0124] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the radius of the dissociated matrix is 4 μm.
[0125] Example 7
[0126] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the mass ratio of the first lithium-rich particles, the second lithium-rich particles and the third lithium-rich particles is 100:10:10.
[0127] Example 8
[0128] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the mass ratio of the first lithium-rich particles, the second lithium-rich particles and the third lithium-rich particles is 100:30:50.
[0129] Example 9
[0130] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the ratio of the length of the one-dimensional support body to the radius of the dissociation matrix is 10:1.
[0131] Example 10
[0132] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the ratio of the length of the one-dimensional support body to the radius of the dissociation matrix is 2:1.
[0133] Embodiment 11
[0134] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the mass ratio of the lithium-rich particles, the dissociated matrix, and the one-dimensional support is 100:10:1.
[0135] Example 12
[0136] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the mass ratio of the lithium-rich particles, the dissociated matrix, and the one-dimensional support is 100:30:10.
[0137] Example 13
[0138] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the lithium-rich particles are replaced with lithium malonate.
[0139] Embodiment 14
[0140] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the material of the one-dimensional support is replaced by TiO2.
[0141] Embodiment 15
[0142] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the composite lithium supplement material does not include a one-dimensional support body.
[0143] Comparative Example 1
[0144] This comparative example provides lithium-rich particles Li2C2O4.
[0145] Comparative Example 2
[0146] This comparative example provides a composite lithium supplement material. The difference between this comparative example and Example 1 is that the lithium-rich particles have only one particle size of 1 μm.
[0147] Comparative Example 3
[0148] This comparative example provides a composite lithium supplement material. The difference between this comparative example and Example 1 is that the first lithium-rich particles, the second lithium-rich particles, and the third lithium-rich particles are mixed and agglomerated to form an inner core, and the dissociated material is coated on the outer surface of the inner core.
[0149] The parameters of the composite lithium supplement materials provided by Examples 1 to 15 and Comparative Examples 1 to 3 are shown in Table 1:
[0150] Table 1 Parameters of composite lithium supplement materials provided in Examples and Comparative Examples
[0151]
[0152]
[0153] The composite lithium supplement materials provided in the above-mentioned Examples 1 to 15 and the composite lithium supplement materials provided in Comparative Examples 1 to 3 are respectively assembled into positive electrode sheets and lithium-ion batteries according to the following methods:
[0154] Positive electrode sheet: The composite lithium supplement material, SP and PVDF are mixed in a mass ratio of 90:4:6 to form a positive electrode slurry, the positive electrode slurry is coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a positive electrode sheet;
[0155] Negative electrode: lithium sheet;
[0156] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte, and the concentration of LiPF6 was 1 mol / L;
[0157] Diaphragm: Polypropylene microporous separator;
[0158] Lithium-ion battery assembly: Assemble button-type lithium-ion full batteries in an inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.
[0159] The electrochemical performance of each lithium-ion battery assembled in the above lithium-ion battery embodiment was tested under the following test conditions:
[0160] The battery was charged at a rate of 0.1C with a cut-off voltage of 4.7V. The battery was charged at a constant voltage with a cut-off voltage of 4.7V. After the charging process was completed, the battery was allowed to stand for 10 minutes and then discharged at a rate of 0.1C with a cut-off voltage of 2.5V. The charging platform was observed during the charging process to obtain the decomposition voltage of the composite lithium supplement material.
[0161] The positive electrode slurry was mixed into a test sample with a solid content of 80%, and then the viscosity was tested using a viscometer. The test results of the lithium battery and the positive electrode slurry are shown in Table 2 below:
[0162] Table 2. Test results of embodiments and comparative examples
[0163]
[0164]
[0165] From the test results of Example 1, Comparative Example 1 and Comparative Example 3 in Table 2, it can be seen that the simple lithium-rich particles in the absence of a catalyst (Comparative Example 1) basically cannot release the capacity, and the viscosity of the slurry is also relatively large; when the lithium-rich particles have only one particle size (Comparative Example 2), the capacity is relatively low, but due to the encapsulation of the dissociation material, the viscosity of the slurry is slightly reduced; when lithium-rich particles of different particle sizes are used (Comparative Example 3), since the decomposition of the composite lithium supplement material becomes simple, the decomposition voltage and overpotential are further reduced, and the slurry viscosity is also further reduced, but due to the presence of the one-dimensional support body in Comparative Examples 2 and 3, the slurry viscosity is significantly reduced relative to Comparative Example 1.
[0166] At the same time, it can be seen from the test results of Example 1, Comparative Example 1 and Comparative Example 3 in Table 2 that the dissociated matrix will cause the lithium-rich particles to slowly release lithium, so in the tests of Example 1 and Comparative Example 3, the battery still has capacity release after 100 cycles of charge and discharge. The lithium ions in the composite lithium supplement material are continuously released during the subsequent multiple cycles of charging, so that the composite lithium supplement material has a sustained release characteristic, which can continuously replenish the active lithium lost by the battery, achieve the purpose of full life cycle lithium supplement, and improve the cycle stability of the battery, thereby maintaining the abundance of lithium ions in the battery system, and ensuring that the battery material has the characteristics of high capacity and long cycle. In addition, in the scheme provided by the present invention (Example 1), the battery has a higher capacity retention rate after 100 cycles, which also illustrates that the structure of the composite lithium supplement material provided by the present invention has a better slow lithium release effect.
[0167] From the test results of Example 1, Example 2, Example 3 and Implementation 4 in Table 2, it can be seen that when the lithium-rich particles are evenly distributed, the internal distribution of the composite lithium-supplementing material is relatively even, so the decomposition voltage of the material will be relatively increased, and the narrow particle size distribution will also increase the decomposition voltage of the composite lithium-supplementing material and reduce the capacity. However, if there is no third lithium-rich particle, the proportion of large lithium-rich particles increases, the decomposition voltage of the composite lithium-supplementing material increases, and the capacity decreases. At the same time, since the proportion of the second lithium-rich particles also increases, the agglomeration effect of the composite lithium-supplementing material is enhanced and the slurry viscosity increases. At the same time, the particle size distribution of the lithium-rich particles has an impact on the lithium release effect of the composite lithium-supplementing material, which is manifested in that the battery 100 cycle capacity retention rate fluctuates due to the particle size distribution of the lithium-rich particles.
[0168] From the test results of Example 1, Example 5 and Implementation 6 in Table 2, it can be seen that when the dissociated matrix is large, due to the high proportion of the dissociated matrix, the conductivity of the material decreases, the decomposition voltage of the material increases, and the capacity decreases, but the composite lithium supplement material will be more persistent and the effect of slow lithium release will be enhanced. When the dissociated matrix is small, the composite lithium supplement material decomposes faster and has a higher capacity, but due to the weakened coating effect of the matrix, the viscosity of the material slurry increases, and the decomposition of the composite lithium supplement material is accelerated, and the effect of slow lithium release is weakened.
[0169] From the test results of Example 1, Example 7 and Example 8 in Table 2, it can be seen that when the content of the second lithium-rich particles and the third lithium-rich particles is low, due to the large number of large lithium-rich particles, decomposition is difficult, the decomposition voltage is high, and the capacity is low, but it will cause the composite lithium-supplementing material to exist for a long time, and the slow release of lithium will be enhanced. However, due to the large particles, the agglomeration is not serious, and the slurry viscosity is low. When the content of the second lithium-rich particles and the third lithium-rich particles is too high, due to the large number of small lithium-rich particles, decomposition is easy, the decomposition voltage is low, and the capacity is high, it will also cause the decomposition of the composite lithium-supplementing material to be accelerated, and the slow release of lithium will be weakened. However, due to the small particles, the agglomeration is very serious, and the slurry viscosity increases.
[0170] From the test results of Example 1, Example 9 and Example 10 in Table 2, it can be seen that when the radius ratio of the one-dimensional support and the dissociation matrix is too large, although it can better catalyze the decomposition of the composite lithium supplement material and reduce the viscosity of the slurry, it will cause the compaction density of the material to decrease, resulting in a decrease in the actual proportion of the composite lithium supplement material, thereby causing the capacity of the composite lithium supplement material to be relatively reduced. When the radius ratio of the one-dimensional support and the dissociation matrix is too small, on the one hand, the catalytic effect is weak, resulting in a high decomposition voltage of the composite lithium supplement material and a reduced capacity, and on the other hand, the viscosity reduction effect is weakened, and the viscosity of the material increases.
[0171] It can be seen from the test results of Example 1, Example 11 and Example 12 in Table 2 that when the proportion of the dissociated material and the one-dimensional support is small, the capacity of the composite lithium supplement material is difficult to release, the decomposition voltage is increased, and the viscosity of the slurry is increased. When the proportion of the dissociated material and the one-dimensional support is too large, although the structural advantage reduces the decomposition voltage and viscosity of the composite lithium supplement material, the mass proportion of the composite lithium supplement material is too small, which also leads to a decrease in the capacity of the composite lithium supplement material.
[0172] From the test results of Example 1, Example 13 and Implementation 14 in Table 2, it can be seen that the solution provided by the present invention is also applicable to catalysts of other one-dimensional supports, and can achieve the effect of reducing the decomposition voltage, increasing the lithium supplement capacity, and reducing the slurry viscosity. At the same time, the one-dimensional support as a catalyst only affects the decomposition voltage and slurry viscosity (affected by the aspect ratio) of the material, and the material type of the one-dimensional support and the lithium-rich particles does not affect the overall slow release of lithium of the composite lithium supplement material, which also illustrates that the solution provided by the present invention is an improvement in the material structure and can be applied to most types of material compositions.
[0173] From the test results of Example 1 and Example 15 in Table 2, it can be seen that in the absence of a one-dimensional support, the slurry viscosity of Example 15 increases sharply compared with that of Example 1, indicating that the one-dimensional support has a significant viscosity reducing effect.
[0174] In the description of the embodiments of the present invention, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0175] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope covered by the present invention.
Claims
1. A composite lithium supplement material, characterized in that: It comprises a plurality of lithium-rich particles and a dissociation matrix, wherein the plurality of lithium-rich particles are distributed in the dissociation matrix, the particle sizes of the plurality of lithium-rich particles are not all the same, and the plurality of lithium-rich particles release lithium in sequence as the dissociation matrix dissociates.
2. The composite lithium supplement material according to claim 1, characterized in that: The lithium-rich particles at least include first lithium-rich particles and second lithium-rich particles, and the particle size of the first lithium-rich particles is larger than the particle size of the second lithium-rich particles; The first lithium-rich particles and the second lithium-rich particles are randomly distributed in the dissociation matrix, or, Along the direction from the center to the surface of the dissociation matrix, the second lithium-rich particles are distributed on the periphery of the first lithium-rich particles.
3. The composite lithium supplement material according to claim 2, characterized in that: The lithium-rich particles also include at least third lithium-rich particles, the particle size of the third lithium-rich particles is larger than the particle size of the second lithium-rich particles and smaller than the particle size of the first lithium-rich particles, and along the direction from the center to the surface of the dissociation matrix, the third lithium-rich particles are distributed on the periphery of the first lithium-rich particles, and the second lithium-rich particles are distributed on the periphery of the third lithium-rich particles.
4. The composite lithium supplement material according to claim 2 or 3, characterized in that: The particle size of the lithium-rich particles satisfies at least two of the following: 50 nm to 10 μm; and / or The particle size of the first lithium-rich particles satisfies at least one of 100 nm to 5 μm; and / or The particle size of the second lithium-rich particles satisfies at least one of 50 nm to 1 μm; and / or The mass ratio of the first lithium-rich particles to the second lithium-rich particles is 100:(10-50).
5. The composite lithium supplement material according to claim 1, characterized in that: The dissociation matrix includes a plurality of coating layers, which together form a multi-layer core-shell structure, and each of the coating layers is dispersedly filled with lithium-rich particles.
6. The composite lithium supplement material according to claim 1, characterized in that: The composite lithium supplement material also includes a plurality of one-dimensional supports extending from the surface of the dissociation matrix, one end of the one-dimensional support extending into the thermal dissociation matrix to connect with the lithium-rich particles, and the other end of the one-dimensional support extending outward away from the dissociation matrix.
7. The composite lithium supplement material according to claim 6, characterized in that: The dissociation matrix includes one or more of a high molecular polymer, a metal compound, and a carbon material; and / or The dissociation matrix is a porous structure, and the porosity of the dissociation matrix is 50% to 90%; and / or The one-dimensional support comprises metal oxide and / or metal element and / or carbon material; and / or The ratio of the length of the one-dimensional support to the radius of the dissociation matrix is (2-10):1; and / or The mass ratio of the lithium-rich particles, the dissociated matrix, and the one-dimensional support is 100:(10-30):(1-10).
8. A method for preparing a composite lithium supplement material, characterized in that: include: The lithium-rich material and ball milling beads with different diameters are mixed and ball-milled to obtain a plurality of lithium-rich particles with different particle sizes; The plurality of lithium-rich particles are mixed with a dissociation material precursor so that the plurality of lithium-rich particles are distributed in the dissociation matrix.
9. A positive electrode material, characterized in that: The positive electrode material includes an active material and a composite lithium-replenishing material, and the composite lithium-replenishing material includes the composite lithium-replenishing material according to any one of claims 1 to 7, or includes the composite lithium-replenishing material obtained by the preparation method of the composite lithium-replenishing material according to claim 8.
10. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the positive electrode material as claimed in claim 9.